Tacho-less Order Tracking for Gearbox based on Time-varying Filter and CWT - Shuangxi Jing; Zhipeng Luo; Junfa Leng; Zhiyang Wang (Jixie chuandong)
In the fault diagnosis of complex gearbox system under the rotation frequency fluctuation，the orders of meshing frequency interfere with one another，so it is difficult to estimate gear meshing frequency. For this problem，a tacho-less order tracking technique combining with time-varying filter and continuous wavelet transform（CWT） is proposed. Time varying filter is set based on short-time Fourier transform（STFT）. The smooth instantaneous frequency estimation（IFE） is obtained based on time-varying filter and CWT. The phase of the reference shaft is calculated with Vold-Kalman filter（VKF）. The order spectrum obtained by the proposed method is basically consistent of the computed order tracking（COT）. Lastly，the position of fault gear can be accurately judged by Fast-kurtogram algorithm. The results of simulation and experiment show that the proposed method can provide a new effective method for mechanical fault diagnosis under the condition of strong noise and apparent speed variation.